Toward the design of highly stable small colloidal SERS substrates with supramolecular host-guest interactions for ultrasensitive detection - Fraire, Juan Carlos (2015)
In this work, we report a simple strategy to obtain ultrasensitive SERS nanostructures by self-assembly of Au nanospheres (NSs). This novel protocol allow us to obtain in a reproducible manner Au NS dimers using cucurbit[6]uril (CB[6]) molecules as linkers. The resulting dimers are stable in colloidal dispersion over several days, generating in this way nanostructures with highly reproducible hot spots. This feature is due to the precise subnanometric control of the molecules that generates interparticle distance and, at the same time, of the capability of placing analyte molecules just within these junctions of ultrahigh field enhancement due to the host-guest properties of the CB[6] molecule. The dimer formation is based on the modification of the metal surface with cysteamine molecules (Cys) previous incubation with CB[6] molecules. The cysteamine-functionalized NSs (Cys/NSs) are positive charged due to the protonation of the amine groups of the Cys molecule at the working pH. These positive groups interact through H-bonds with the carbonyls groups at the portal of the CB[6] molecules. The dimer formation is based on the stoichiometric control between Cys/NPs and CB[6] (ratio 2:1), generating a gap of 1.8 nm and giving rise to SERS enhancements of around 108. The host-guest properties of the CB[6] molecule are used to detect the average SERS enhancement produced by adding methyl viologen (MV) as plasmonic probe. It was found that the average analytical enhancement factor (AEF) for MV is as good as that obtained for the CB[6] itself (around 108).